Polynomial Relations for q-Characters via the ODE/IM Correspondence - Sun, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
Let Uq(b) be the Borel subalgebra of a quantum affine algebra of type X⁽¹⁾n (X=A,B,C,D). Guided by the ODE/IM correspondence in quantum integrable models, we propose conjectural polynomial relations among the q-characters of certain representations of Uq(b).